Block Preconditioned SSOR Methods for -Matrices Linear Systems - Zhao-Nian Pu; Xue-Zhong Wang (Journal of Applied Mathematics)
We present a block preconditioner and consider block preconditioned SSOR iterative methods for solving linear system . When is an -matrix, the convergence and some comparison results of the spectral radius for our methods are given. Numerical examples are also given to illustrate that our methods are valid.